PENGARUH JOB DEMANDS TERHADAP WORK ENGAGEMENT MELALUI BURNOUT KARYAWAN INDUSTRI MANUFAKTUR DI SALATIGA - Mokhammad Khukaim Barkhowa; Tri Widodo (Sekolah Tinggi Ilmu Ekonomi Semarang, 2020)
Work engagement affects several aspects of the company. Work engagement is the latest issue in managing human resources (HR). Work engagement is the latest issue in managing human resources (HR). Work engagement is defined as a positive and satisfying mental state related to work characterized by vigor, dedication, and absorption. One maximal work attitude in contributing as a predictor of institutional performance is engagement. The purpose of this study was to analyze the effect of job demands on work engagement through burnout as an intervening variable. The sample of this study was 100 respondents. Sampling using snowball sampling is a sampling technique that first starts with a small amount and then enlarges. Data analysis using multiple linear regression models, simple linear regression and sobel tests. The results of hypothesis testing job demands negatively affect the work engagement, burnout negatively affect the work engagement, job demand positive effect on burnout, job demand affect the work engagement through burnout